(untitled) (Jurnal Simki Economic, 2025)
Parking is one of the income potentials of an area, including Malang City, which has 950 parking spots. The income from parking user charges in Malang City has an upward trend each year. On the other hand, the management of parking user charges is very complicated because it involves several actors, both formal and informal. This research aims at finding out the mechanism for managing parking user charges and the role of the actors involved. This research uses qualitative method. Data collection was carried out using primary and secondary surveys through interviews and observations. The result shows that the parking implementation in Malang City is not supported by the regulations that in depth discuss about the mechanism for collecting and depositing the parking user charges. It is evidenced by the lack of mayoral regulations concerning parking management in Malang City. Apart from that, the limited resources of supervisory apparatus from Transportation Office may trigger the emergence of parking user charge leakage.